1984
DOI: 10.1159/000183315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diets Containing Varying Concentrations of Essential Fatty Acids and Triglycerides on Renal Function in Uremic Rats and NZB/NZW F<sub>1</sub> Mice

Abstract: Influences of essential fatty acids (EFA) and triglycerides as reasons for the progression of chronic renal failure are still in debate. We studied the outcome of four diets containing different concentrations of triglycerides and EFA in 5/6 nephrectomized rats and in NZB/W mice up to 45 weeks. The results showed no significant differences in the outcome of survival rate, proteinuria, urea, and creatinine levels as well as histological findings in the different groups of both animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The amount of lipid added in our experiment was maximally 25%, while Kelley and Izui [8] gave 50% lipid which may explain the difference in results. Hirschberg et al [22], who also used less than 25% lipid in their experiments, found no influence on the renal histology in NZB/W from the total amount of lipids or of esterified fatty acids.…”
Section: Discussionmentioning
confidence: 91%
“…The amount of lipid added in our experiment was maximally 25%, while Kelley and Izui [8] gave 50% lipid which may explain the difference in results. Hirschberg et al [22], who also used less than 25% lipid in their experiments, found no influence on the renal histology in NZB/W from the total amount of lipids or of esterified fatty acids.…”
Section: Discussionmentioning
confidence: 91%
“…Many studies have compared these two sources of prostaglandins (those from dienoic series with those of trienoic series) but with inconclusive results (5-7). Studies using different experimental models such as a 5/6 reduction of renal mass, lupus nephritis, and immunologic glomerulonephritis have suggested that increases in vasodilatory prostaglandins could retard the progression of CRF (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%